Gradient grain ultra-low carbon steel and preparation method and application thereof
By using the use of microwave high -temperature experimental furnaces and surface micro -deformation technology in ultra -low -carbon micro -alloy steel to prepare ultra -low -carbon steel with gradient grain size, it solves the lack of performance of the metal and fracture of the heart cubic structure under the low temperature environment. The problem has achieved efficient preparation of gradient structural materials.
Patent Information
- Application Number
- CN202411467176.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to improve fracture resistance for face-centered cubic structure metals under low temperature environments, and the preparation method of gradient structure metals has the problem that the surface gradient characteristics are not retained.
The inhalation heating principle of microwave high -temperature experimental oven is adopted, combined with the micro -deformity of the material surface, and through solid -soluble treatment, rolling, and multiple ignition treatment, it is prepared to prepare ultra -low -carbon micro -alloy steel with grain gradient distribution.
The grain size of the ultra -low -carbon steel gradually transitions from the surface to the heart. The gradient area is larger, which improves the fracture performance of the material, and simplifies the preparation process and reduces the cost.
Smart Images

Figure BDA0005093703030000111 
Figure HDA0005093703040000011 
Figure HDA0005093703040000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gradient material preparation, and specifically relates to a gradient grain ultra-low carbon steel and a preparation method and application thereof. Background Art
[0002] With the development of the marine economy and the exploitation of deep-sea resources, it is a major challenge to develop high-performance steel for offshore platforms with excellent fracture resistance. This is especially important for low-alloy steels with a body-centered cubic (bcc) structure, because they may lose a lot of ductility and toughness below the ductile-brittle transition temperature (DBTT). In contrast, face-centered cubic metals have more excellent properties, but in low-temperature environments, face-centered cubic structured metals have poor toughness, and to improve their performance, more expensive alloying elements must be added. Over the past few decades, the gradient structures found in biomaterials have been a source of inspiration for scientists seeking to improve the performance of metals and alloys. Compared with similar materials, these gradient structured metals have excellent mechanical properties.
[0003] In the prior art, the preparation method of gradient structure metal is mainly surface mechanical treatment, which causes severe plastic deformation on the surface. In this process, the surface of the sample is easily damaged, and the gradient characteristics of the gradient structure material obtained by this method are only retained on the surface. Summary of the invention
[0004] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a gradient grain ultra-low carbon steel and its preparation method and application. The present invention utilizes the wave absorption heating principle of a microwave high temperature experimental furnace and combines the micro deformation of the material surface to prepare an ultra-low carbon microalloy steel with a gradient grain size distribution.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] In one aspect, the present invention provides a method for preparing gradient grain ultra-low carbon steel, comprising the following steps:
[0007] S1, subjecting the ultra-low carbon microalloyed steel to solid solution treatment and water cooling;
[0008] The composition mass percentage of the ultra-low carbon microalloyed steel is as follows: Ni: 0.1-0.4%, Cr: 0.1-0.3%, Cu: 0.01-0.5%, Si: 0.1-0.3%, Mn: 1-2%, Mo: 0.001%-0.1%, Al: 0.01-0.5%, Co: 0.001-0.01%, Ti: 0.001-0.1%, Nb: 0.01-0.5%, C≤0.015%, and the remaining components are Fe and other inevitable impurities;
[0009] S2, cutting the water-cooled ultra-low carbon micro-alloyed steel and removing the surface oxide layer to obtain a metal sample;
[0010] S3. After the metal sample is rolled, it is placed in a microwave high-temperature experimental furnace for tempering. The rolling and tempering treatments are repeated, and the total tempering time does not exceed 2 hours.
[0011] The present invention uses a high-temperature experimental microwave oven as a tempering treatment furnace. Unlike the conventional muffle furnace which uses the resistance heating principle, the microwave high-temperature experimental furnace adjusts microwaves through four magnetron power supplies around the furnace. During the heating process, the microwave contacts the surface of the sample, and the auxiliary heating material on the surface of the sample absorbs the microwave and converts it into heat, and then transmits it into the interior of the sample. During this heating process, the heating rate is fast, and only the surface coated with the auxiliary heating material can quickly absorb the wave and convert it into heat for heating. Therefore, its heating method is different from the uniform heating principle of the traditional muffle furnace, and belongs to uneven heating.
[0012] In step S1, the temperature of the solution treatment is 900-1200°C;
[0013] In step S1, the solution treatment time is 1 to 4 hours.
[0014] In step S2, the thickness of the ultra-low carbon microalloyed steel after cutting is 5 mm to 10 mm;
[0015] In step S2, the length and width of the ultra-low carbon micro-alloyed steel after cutting are both 10 mm to 30 mm.
[0016] In step S3, the rolling equipment for the metal sample is an asymmetric rolling experimental equipment, and the rotation speed of the two rollers is 1.5 r / min.
[0017] In step S3, the speeds of the two rollers remain unchanged, and the rolling rate remains the same as the previous rolling rate;
[0018] In step S3, the total rolling passes are 1 to 15 passes;
[0019] In step S3, the single rolling reduction rate is 1% to 20%;
[0020] In step S3, the total reduction ratio does not exceed 50%.
[0021] In step S3, the temperature of the tempering treatment is 400-600°C;
[0022] In step S3, the single tempering time is 5 minutes to 60 minutes.
[0023] In step S3, the maximum power of the microwave high temperature experimental furnace is 4.5KW;
[0024] In step S3, the microwave frequency of the microwave high temperature experimental furnace is 2.45GHZ±50MHz;
[0025] In step S3, the heating rate of the microwave high temperature experimental furnace is 0 to 1000° C. / min;
[0026] In step S3, the auxiliary heating material of the microwave high temperature experimental furnace is silicon carbide;
[0027] In step S3, during the tempering process, the vacuum degree in the microwave high temperature experiment furnace cavity is -0.1Mpa.
[0028] Before step S1, the method further includes:
[0029] The high-purity alloy material is put into a smelting furnace for smelting and pouring according to the proportion to obtain the ultra-low carbon micro-alloy steel.
[0030] In another aspect, the present invention provides a gradient grain ultra-low carbon steel, which is prepared by the above-mentioned preparation method of gradient grain ultra-low carbon steel.
[0031] The third aspect of the present invention also provides gradient grain ultra-low carbon steel prepared by the above-mentioned preparation method of gradient grain ultra-low carbon steel, or the use of the above-mentioned gradient grain ultra-low carbon steel in the manufacture of hull structures of seagoing vessels and inland river vessels.
[0032] The positive and progressive effects of the present invention are:
[0033] 1. The present invention is based on the principle of heat treatment, performs small deformation rolling on the surface of the metal sample, and uses a special heating method of a microwave oven to heat and recrystallize. In this process, the uniformity of the material's structure is guaranteed.
[0034] 2. The grain size of the gradient structure material prepared by the present invention gradually transitions from the surface to the core, and the gradient area is larger.
[0035] 3. The preparation method of the present invention has a short production cycle, simple equipment operation, low cost, safe operating environment, and can achieve mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The preparation process of Examples 1, 2 and 3 of the present invention;
[0037] Figure 2 It is an electron backscattering image of the gradient-grained ultra-low carbon steel prepared in Example 1 of the present invention, wherein Figure a1 is an IPF image of the sample surface, Figure a2 is a grain size image of the sample surface, Figure b1 is an IPF image at 1 / 4 of the sample, Figure b2 is a grain size image at 1 / 4 of the sample, Figure c1 is an IPF image of the sample core, and Figure c2 is a grain size image of the sample core;
[0038] Figure 3 It is an electron backscattering image of the gradient-grained ultra-low carbon steel prepared in Example 2 of the present invention, wherein Figure a1 is an IPF image of the sample surface, Figure a2 is a grain size image of the sample surface, Figure b1 is an IPF image at 1 / 4 of the sample, Figure b2 is a grain size image at 1 / 4 of the sample, Figure c1 is an IPF image of the sample core, and Figure c2 is a grain size image of the sample core;
[0039] Figure 4 The electron backscattering diagram of the gradient-grained ultra-low carbon steel prepared in Example 3 of the present invention, Figure a1 is the IPF diagram of the sample surface, Figure b1 is the grain size diagram of the sample surface, Figure a2 is the IPF diagram of the sample 1 / 4, b2 is the grain size diagram of the sample 1 / 4, Figure a3 is the IPF diagram of the sample core, and Figure b3 is the grain size diagram of the sample core;
[0040] Figure 5 The metallographic images of the sample obtained in Comparative Example 1 of the present invention, wherein Figure a is a metallographic image of the surface of the sample, Figure b is a metallographic image of the structure at 1 / 4 of the sample, and Figure c is a metallographic image of the structure at the core of the sample;
[0041] Figure 6 is a metallographic image of the sample obtained in Comparative Example 2 of the present invention;
[0042] Figure 7 Figure 3 is a metallographic diagram of the sample obtained in Comparative Example 3 of the present invention, Figure a is a metallographic diagram of the surface of the sample, and Figure b is a metallographic diagram of the core;
[0043] Figure 8 1 is a metallographic image of the sample obtained in Comparative Example 4 of the present invention, wherein Figure a is a metallographic image of the surface of the sample, and Figure b is a metallographic image of the core. DETAILED DESCRIPTION
[0044] The present invention is described in detail below in conjunction with the embodiments, and the technical scheme of the present invention is clearly and completely described to facilitate the understanding of the present invention by those skilled in the art. The described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods not mentioned in detail are process steps or preparation methods known to those skilled in the art.
[0045] Figure 1 The experimental operation flow chart shows that the method for preparing the ultra-low carbon microalloyed steel with a grain size gradient structural material of the present invention comprises the following steps:
[0046] (1) Loading: According to the designed composition, the required high-purity alloy material is placed into the furnace mold of the melting furnace. This process should strictly follow the material ratio to ensure that the sample composition is consistent with the design;
[0047] (2) Melting: After placing the smelting material, close and check the furnace to ensure it is sealed. Then evacuate the furnace and slowly increase the induction eddy current to allow the material to melt slowly. When no obvious bubbles are generated, increase the voltage to fully melt the material.
[0048] (3) Pouring: After the material is refined, it can be directly poured under vacuum conditions in the furnace. Samples can be taken after the sample is naturally cooled after pouring.
[0049] (4) Sample pretreatment: The metal sample is heated to 900-1200°C for solution treatment for 1-4 h, and the sample is cut into rectangular blocks with a length and width of 10 mm-20 mm and a thickness of 10 mm-30 mm. The cut samples are polished to remove the surface oxide layer.
[0050] (5) Sample rolling: The processed samples were subjected to small deformation rolling with different reduction rates of 0.1% to 20%. The rolling equipment was an asymmetric rolling experimental equipment with a roll diameter of 180 mm, a roll length of 300 mm, and a maximum rolling pressure of 700 KN.
[0051] (6) Tempering: After rolling, a layer of auxiliary heating material is applied on the upper and lower surfaces of the sample in contact with the rollers, and then placed in a microwave high-temperature experimental furnace for tempering. The tempering temperature is 400-600°C, the tempering time is 5-60 minutes, and the vacuum environment in the furnace is maintained during the tempering process.
[0052] (7) After tempering is completed, repeat steps 5 and 6. The total tempering time of this process shall not exceed 2 hours.
[0053]
Performance test
[0054] The product prepared in the embodiment was tested for its application performance, and the test method is as follows:
[0055] 1. Hardness test: Use 402SXV micro Vickers hardness tester for hardness test.
[0056] 2. Microstructure properties: Microstructure observation was performed using a metallographic microscope Axio Observer DIM from Zeiss.
[0057] 3. Microstructure performance: EBSD test was performed using the American EDAX-TSL instrument. TSL-OIM-Analysis6 was used for data analysis.
[0058] Example 1
[0059] An ultra-low carbon microalloy steel, comprising 0.0065% C, 0.116% Si, 1.508% Mn, 0.154% Cr, 0.084% Mo, 0.211% Cu, 0.02% Al, 0.0067% Co, 0.337% Ni, 0.0064% Ti, 0.025% Nb, and the remainder being Fe and other inevitable impurities.
[0060] Step 1: Loading: According to the designed composition, put the required high-purity alloy material into the furnace mold of the melting furnace. This process should strictly follow the material ratio to ensure that the sample composition is consistent with the design;
[0061] Melting: After placing the smelting material, close and check the furnace to ensure sealing. Then evacuate the furnace and slowly increase the induction eddy current to allow the material to melt slowly. When no obvious bubbles are generated, increase the voltage to fully melt.
[0062] Pouring: After the material is refined, it can be directly poured under vacuum in the furnace. Samples can be taken after the sample is naturally cooled after pouring.
[0063] Step 2: Use a wire cutting machine to cut the sample into ultra-low carbon microalloy samples with a thickness of 10 mm, a width of 10 mm, and a length of 20 mm. Before rolling, the sample is first solution treated to make its structure uniform. The solution treatment temperature is 900 ° C, the holding time is 120 min, and the sample is water-cooled. After the solution treatment, the surface of the sample is mechanically polished to remove the surface oil and oxide film.
[0064] Step 3: Use an asymmetric rolling test equipment to roll the sample, with a two-roll rotation speed of 1.5 r / min and a reduction rate of 2.5%.
[0065] Step 4: After rolling is completed, tempering treatment is carried out in a microwave high temperature experimental furnace. The equipment includes a microwave oven, a vacuum pump, a thermocouple, and a circulating cooling water system. The microwave oven has a total of four sets of magnetic control devices, with a maximum power of 4.5kw and a maximum heating temperature of 1500°C. Due to the special heating method of the microwave high temperature experimental furnace, a layer of absorbing material needs to be coated on its surface. The present invention uses silicon carbide as an absorbing material for auxiliary heating. The heating rate is 80°C / min, the heating temperature is 600°C, and the insulation time is 10min. The heating process and the insulation process ensure a vacuum environment, and the vacuum degree is -0.1MPa.
[0066] Step 5: Repeat steps 3 and 4 in sequence. During this process, the setting conditions of all steps remain unchanged. Repeat 6 times in total. The total tempering time is 2 hours. The total reduction rate is 15%.
[0067] The macroscopic and microstructural properties of the final tempered samples were analyzed, and it was observed that the grain size of the sample from the surface to the core was arranged in a gradient, such as Figure 2During the tempering process, the small deformation rolling on the sample surface causes the sample surface to accumulate stress, providing a driving force for recrystallization for subsequent tempering. During the heating process, the surface layer heats up to the recrystallization temperature before the core, so the grain size of the surface structure is finer.
[0068] Example 2
[0069] An ultra-low carbon microalloy steel, comprising 0.0065% C, 0.116% Si, 1.508% Mn, 0.154% Cr, 0.084% Mo, 0.211% Cu, 0.02% Al, 0.0067% Co, 0.337% Ni, 0.0064% Ti, 0.025% Nb, and the remainder being Fe and other inevitable impurities.
[0070] Step 1: Loading: According to the designed composition, the required high-purity alloy material is placed into the furnace mold of the melting furnace. This process should strictly follow the material ratio to ensure that the sample composition is consistent with the design.
[0071] Melting: After placing the smelting material, close and check the furnace to ensure sealing. Then evacuate the furnace and slowly increase the induction eddy current to allow the material to melt slowly. When no obvious bubbles are generated, increase the voltage to fully melt.
[0072] Pouring: After the material is refined, it can be directly poured under vacuum in the furnace. Samples can be taken after the sample is naturally cooled after pouring.
[0073] Step 2: Use a wire cutting machine to cut the sample into ultra-low carbon microalloy samples with a thickness of 10 mm, a length of 20 mm, and a width of 10 mm. Before rolling, the sample is solution treated to make the structure uniform. The solution treatment temperature is 1200 ° C, the holding time is 120 min, and the sample is water-cooled. After the solution treatment, the surface of the sample is mechanically polished to remove the surface oil and oxide film.
[0074] Step 3: Use an asymmetric rolling test equipment to roll the sample, with a two-roll speed of 1.5 r / min and a reduction rate of 6%.
[0075] Step 4: After rolling is completed, tempering treatment is carried out in a microwave high temperature experimental furnace. The equipment includes a microwave oven, a vacuum pump, a thermocouple, and a circulating cooling water system. The microwave oven has a total of four sets of magnetic control devices, with a maximum power of 4.5kw and a maximum heating temperature of 1500°C. Due to the special heating method of the microwave high temperature experimental furnace, a layer of absorbing material needs to be coated on its surface. The present invention uses silicon carbide as an absorbing material for auxiliary heating. The heating rate is 80°C / min, the heating temperature is 600°C, and the insulation time is 30min. The heating process and the insulation process ensure a vacuum environment. The vacuum degree is -0.1Mpa.
[0076] Step 5: Repeat steps 3 and 4 in sequence. During this process, the setting conditions of all steps remain unchanged. Repeat 4 times in total. The total tempering time is 2 hours. The total reduction rate is 24%.
[0077] The macroscopic and microstructural properties of the final tempered samples were analyzed, and it was observed that the grain size of the sample from the surface to the core was arranged in a gradient, such as Figure 3 During the tempering process, the small deformation rolling on the sample surface causes the sample surface to accumulate stress, providing a driving force for recrystallization for subsequent tempering. During the heating process, the surface layer heats up to the recrystallization temperature before the core.
[0078] Example 3
[0079] A low-cost ultra-low carbon microalloy steel, comprising 0.0065% C, 0.116% Si, 1.508% Mn, 0.154% Cr, 0.084% Mo, 0.211% Cu, 0.02% Al, 0.0067% Co, 0.337% Ni, 0.0064% Ti, 0.025% Nb, and the remaining components are Fe and other inevitable impurities.
[0080] Step 1: Loading: According to the designed composition, the required high-purity alloy material is placed into the furnace mold of the melting furnace. This process should strictly follow the material ratio to ensure that the sample composition is consistent with the design.
[0081] Melting: After placing the smelting material, close and check the furnace to ensure sealing. Then evacuate the furnace and slowly increase the induction eddy current to allow the material to melt slowly. When no obvious bubbles are generated, increase the voltage to fully melt.
[0082] Pouring: After the material is refined, it can be directly poured under vacuum in the furnace. Samples can be taken after the sample is naturally cooled after pouring.
[0083] Step 2: Use a wire cutting machine to cut the sample into ultra-low carbon microalloy samples with a thickness of 10 mm, a length of 20 mm, and a width of 10 mm. Before rolling, the sample is first solution treated to make the structure uniform. The solution treatment temperature is 1200 ° C, the holding time is 120 min, and the sample is water-cooled. After the solution treatment, the surface of the sample is mechanically polished to remove the surface oil and oxide film.
[0084] Step 3: Use an asymmetric rolling test equipment to roll the sample, with the two rollers rotating at 1.5 r / min and a reduction rate of 10%.
[0085] Step 4: After rolling is completed, tempering treatment is carried out in a microwave high temperature experimental furnace. The equipment includes a microwave oven, a vacuum pump, a thermocouple, and a circulating cooling water system. The microwave oven has a total of four sets of magnetic control devices, with a maximum power of 4.5kw and a maximum heating temperature of 1500°C. Due to the special heating method of the microwave high temperature experimental furnace, a layer of absorbing material needs to be coated on its surface. The present invention uses silicon carbide as an absorbing material for auxiliary heating. The heating rate is 100°C / min, the heating temperature is 600°C, and the insulation time is 30min. The heating process and the insulation process ensure a vacuum environment. The vacuum degree is -0.1MPa.
[0086] Step 5: Repeat steps 3 and 4 in sequence. During this process, the setting conditions of all steps remain unchanged. Repeat 4 times in total. The total tempering time is 2 hours. The total reduction rate is 40%.
[0087] The macroscopic and microstructural properties of the final tempered samples were analyzed, and it was observed that the grain size of the sample from the surface to the core was arranged in a gradient, such as Figure 4 During the tempering process, the small deformation rolling on the sample surface causes the sample surface to accumulate stress, providing a driving force for recrystallization for subsequent tempering. During the heating process, the surface layer heats up to the recrystallization temperature before the core.
[0088] Comparative Example 1
[0089] Step 1: Use a 20 mm thick ultra-low carbon microalloy sample, the composition of which is consistent with that of Example 1. Before rolling, the sample is solution treated at 900°C for 2 h to make its structure uniform. After solution treatment, the surface of the sample is mechanically polished to remove surface oil and oxide film.
[0090] Step 2: Use an asymmetric rolling test equipment to roll the sample, with a two-roll speed of 1.5 r / min and a reduction rate of 5%;
[0091] Step 3: After rolling, the sample is tempered in a conventional heat treatment tube furnace. The heating temperature is 600°C and the holding time is half an hour. During this process, argon gas is introduced. After tempering, the sample is taken out and air-cooled to room temperature.
[0092] Step 4: Repeat steps 2 and 3. Repeat four times in total, with a total tempering time of 2 hours and a total reduction rate of 20%.
[0093] The macroscopic and microstructural properties of the tempered samples were analyzed and it was observed that there was no significant change in the grain size difference from the surface to the core of the sample, and the structure was uniform. Figure 5 .
[0094] Comparative Example 2
[0095] Step 1: Use a 20 mm thick ultra-low carbon microalloy sample with the same composition as in Example 1.
[0096] Step 2: The sample after solution treatment is polished with sandpaper to remove the surface oxide layer.
[0097] Step 3: Place the sample into the Q376 hook-type shot blasting machine for shot blasting for 20 minutes.
[0098] Step 4: Cut the sample treated with shot peening from the cross section and observe its structural changes. Figure 6 .
[0099] Comparative Example 3
[0100] Compared with Example 1, the only difference is that the composition of the ultra-low carbon microalloyed steel is: C: 0.063%, Si: 0.174%, Mn: 1.578%, Cr: 1.131%, Cu: 0.058%, Al: 0.017%, Ni: 0.136%, and the remaining components are Fe and unavoidable impurities. Figure 7 .
[0101] Comparative Example 4
[0102] Compared with Example 1, the only difference is that in step 2, the thickness of the ultra-low carbon microalloy sample is 30 mm. Figure 8 .
[0103] The microstructures and properties of the steels prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested. The microstructures of the examples and comparative examples of the present invention were all tempered ferrite bainite. The hardness was measured using a Vickers hardness tester, and the grain size of the microstructure samples after rolling, tempering or shot peening was statistically analyzed.
[0104] Table 1 shows the test results of grain size and hardness of steel samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 at different depths after rolling and tempering and shot peening.
[0105] Table 1
[0106]
[0107]
[0108] As can be seen from Table 1, the grain size and hardness of the marine steel after small deformation rolling and tempering show a gradient structure distribution from the surface to the core. As the depth from the surface increases, the grain size gradually increases, and the hardness gradually decreases. The grain size near the surface is smaller, while the grain size in the core is larger, which can reduce the stress concentration at the crack tip and prevent the crack from extending.
[0109] In Example 1, the difference in grain size from the surface to the core is close to 3 μm, and the hardness difference is about 20 HV; in Example 2, the difference in grain size from the surface to the core of the sample is close to 2.5 μm, and the hardness difference is about 17 HV; in Example 3, the difference in grain size from the surface to the core of the sample is close to 2.5 μm, and the hardness difference is about 15 HV. It can be seen that the method described in the present invention can prepare shipbuilding steel with a grain size gradient structure.
[0110] In Comparative Example 1, the difference in grain size from the surface to the core of the sample is not obvious, and the hardness does not change, and there is almost no difference in grain size gradient and gradient performance. Due to the slow tempering heating rate of the conventional tubular furnace, the sample has no obvious gradient.
[0111] In Comparative Example 2, there is no obvious change in the surface of the sample after shot peening. During the shot peening process, the residual stress formed on the surface is recovered in the subsequent process, and the surface structure has no obvious change.
[0112] In Comparative Example 3, the difference in grain size from the surface to the core of the sample is not obvious, and the hardness does not change. There is almost no difference in grain size gradient and gradient performance.
[0113] In Comparative Example 4, the difference in grain size from the surface to the core of the sample is not obvious, and the hardness does not change. There is almost no difference in grain size gradient and gradient performance.
[0114] The shipbuilding steel prepared by the present invention has a gradient structure and performance. This is mainly because the present invention adopts a microwave tempering process, which works together with a small surface deformation during the tempering process to obtain a gradient structure shipbuilding steel with a fine surface grain size and a coarse core grain size. In addition, the present invention has a simple operation process, shortens the time required for the preparation of conventional gradient materials, and has broad application prospects.
[0115] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and equivalent changes made by using the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing gradient grain ultra-low carbon steel, characterized in that: The following steps are involved: S1, subjecting the ultra-low carbon microalloyed steel to solid solution treatment and water cooling; The composition mass percentage of the ultra-low carbon microalloyed steel is as follows: Ni: 0.1-0.4%, Cr: 0.1-0.3%, Cu: 0.01-0.5%, Si: 0.1-0.3%, Mn: 1-2%, Mo: 0.001%-0.1%, Al: 0.01-0.5%, Co: 0.001-0.01%, Ti: 0.001-0.1%, Nb: 0.01-0.5%, C≤0.015%, and the remaining components are Fe and other inevitable impurities; S2, cutting the water-cooled ultra-low carbon micro-alloyed steel and removing the surface oxide layer to obtain a metal sample; S3. After the metal sample is rolled, it is placed in a microwave high-temperature experimental furnace for tempering. The rolling and tempering treatments are repeated, and the total tempering time does not exceed 2 hours.
2. The method for preparing gradient grain ultra-low carbon steel according to claim 1, characterized in that: In step S1, the temperature of the solution treatment is 900-1200°C; And / or, the solution treatment time is 1 to 4 hours.
3. The method for preparing gradient grain ultra-low carbon steel according to claim 1, characterized in that: In step S2, the thickness of the ultra-low carbon microalloyed steel after cutting is 5 mm to 10 mm; And / or, after cutting, the length and width of the ultra-low carbon micro-alloyed steel are both 10 mm to 30 mm.
4. The method for preparing gradient grain ultra-low carbon steel according to claim 1, characterized in that: In step S3, the rolling equipment for the metal sample is an asymmetric rolling experimental equipment, and the rotation speed of the two rollers is 1.5 r / min.
5. The method for preparing gradient grain ultra-low carbon steel according to claim 4, characterized in that: In step S3, the speeds of the two rollers remain unchanged, and the rolling rate remains the same as the previous rolling rate; and / or, the total number of rolling passes is 1 to 15; and / or, a single rolling reduction rate of 1% to 20%; and / or, the total reduction does not exceed 50%.
6. The method for preparing gradient grain ultra-low carbon steel according to claim 1, characterized in that: In step S3, the temperature of the tempering treatment is 400-600°C; And / or, the single tempering time is 5 minutes to 60 minutes.
7. The method for preparing gradient grain ultra-low carbon steel according to claim 1, characterized in that: In step S3, the maximum power of the microwave high temperature experimental furnace is 4.5KW; And / or, the microwave frequency of the microwave high temperature experimental furnace is 2.45GHZ±50MHz; And / or, the heating rate of the microwave high temperature experimental furnace is 0 to 1000°C / min; And / or, the auxiliary heating material of the microwave high temperature experimental furnace is silicon carbide; And / or, during the tempering process, the vacuum degree in the microwave high temperature experiment furnace cavity is -0.1Mpa.
8. The method for preparing gradient grain ultra-low carbon steel according to claim 1, characterized in that: Before step S1, the method further includes: The high-purity alloy material is put into a smelting furnace for smelting and pouring according to the proportion to obtain the ultra-low carbon micro-alloy steel.
9. A gradient grain ultra-low carbon steel, characterized in that: The steel is prepared by the method for preparing gradient grain ultra-low carbon steel as described in claims 1 to 8.
10. Use of the gradient grain ultra-low carbon steel prepared by the preparation method of the gradient grain ultra-low carbon steel as claimed in claims 1 to 8, or the gradient grain ultra-low carbon steel as claimed in claim 9 in manufacturing the hull structure of seagoing vessels and inland waterway vessels.
Citation Information
Cited By
Reaming die for bearing ring production and machining treatment technology of reaming die
CN120169950A